Genetics, genomics and breeding of groundnut (Arachis hypogaea L.). (29th August 2018) - Desmae, Haile; Janila, Pasupuleti; Okori, Patrick; Pandey, Manish K.; Motagi, Babu N.; Monyo, Emmanuel; Mponda, Omari; Okello, David; Sako, Dramane; Echeckwu, Candidus; Oteng‐Frimpong, Richard; Miningou, Amos; et al.
Abstract: Groundnut is an important food and oil crop in the semiarid tropics, contributing to household food consumption and cash income. In Asia and Africa, yields are low attributed to various production constraints. This review paper highlights advances in genetics, genomics and breeding to improve the productivity of groundnut. Genetic studies concerning inheritance, genetic variability and heritability, combining ability and trait correlations have provided a better understanding of the crop's genetics to develop appropriate breeding strategies for target traits. Several improved lines and sources of variability have been identified or developed for various economically important traits through conventional breeding. Significant advances have also been made in groundnut genomics including genome sequencing, marker development and genetic and trait mapping. These advances have led to a better understanding of the groundnut genome, discovery of genes/variants for traits of interest and integration of marker‐assisted breeding for selected traits. The integration of genomic tools into the breeding process accompanied with increased precision of yield trialing and phenotyping will increase the efficiency and enhance the genetic gain for release of improved groundnut varieties.